P23. Basal ganglia pathology in amyotrophic lateral sclerosis is associated with cognitive and behavioural changes. Issue 8 (August 2015) - Machts, J.; Loewe, K.; Kaufmann, J.; Jakubiczka, S.; Abdulla, S.; Petri, S.; Dengler, R.; Heinze, H.-J.; Schoenfeld, M.A.; Vielhaber, S.; Bede, P.
<x xml:space="preserve">Abstract</x> Introduction Extrapyramidal, cognitive, and sensory deficits are increasingly recognised in patients with amyotrophic lateral sclerosis (ALS), suggesting dysfunction of specific frontostriatal, nigrostriatal and corticobasal circuits. While significant basal ganglia involvement has been demonstrated by recent histopathology and neuroimaging studies, subcortical pathology in ALS has not been studied in relation to cognitive and behavioural deficits. Here, we evaluate basal ganglia involvement along the continuum of ALS, ALS with cognitive and behavioural deficits, and ALS with comorbid frontotemporal dementia (ALS-FTD), using multiple, complementary imaging techniques. Methods Volumetric, shape, and density analyses were performed for seven subcortical structures: thalamus, amygdala, nucleus accumbens, hippocampus, caudate nucleus, pallidum, and putamen. Patients were allocated into three study-groups: C9orf72-negative ALS patients without cognitive or behavioural impairment ("ALS-Nci", n = 42), ALS patients with cognitive and/or behavioural impairment ("ALS-Plus", n = 18), and ALS patients with comorbid FTD ("ALS-FTD", n = 7), matched for disease duration and severity. An age-, gender-, and education matched group of healthy controls was also included ("HC", n = 39). Results Volumetric analyses revealed intergroup differences for six subcortical structures when adjusting for total intracranial volume and controlling for age: caudate nucleus (p = 0.023), thalamus (p < 0.001), nucleus accumbens (p < 0.001), hippocampus (p < 0.001), putamen (p < 0.001), and pallidum (p = 0.033). No amygdala volume differences were observed between study-groups (p = 0.406). However, shape analysis revealed right ventral amygdala atrophy in the ALS-Nci group compared to controls (p < 0.05, corrected for multiple comparisons). Hippocampal atrophy was identified in ALS-Plus patients in comparison to controls, affecting the head and body of both hippocampi. Extensive shape differences were detected in the ALS-FTD group compared to all other groups in the bilateral thalami, caudate nuclei, putamina, pallida, hippocampi, and accumbens nuclei. Grey matter density reductions in ALS-Nci were detectable in the frontal lobe and cerebellum (p < 0.05, corrected for multiple comparisons). In accordance with the volumetric findings, a trend of density reduction was also observed in ALS-Plus patients in both hippocampi (p < 0.001, uncorrected). In the ALS-FTD group widespread grey matter atrophy was identified as compared to all other study-groups, affecting the basal ganglia as well as cortical regions (cerebellum, frontal lobes, temporal lobes). Conclusion A gradient of incremental basal ganglia pathology was observed across the ALS/ALS-FTD spectrum, suggesting that the degree of subcortical grey matter pathology in C9orf72-negative ALS is closely associated with cognitive and behavioural changes. The observed changes in shape and lesion location are indicating a disease specific degeneration of subcortical structures and suggest the disruption of frontrostriatal and corticobasal circuits in ALS.